Model-checking a group membership protocol for TDMA-based networks with both static and dynamic scheduling - Valério Rosset (2006)
We report ongoing work on a group membership protocol specially designed to take advantage of the support of both static and dynamic scheduling in new TDMA-based protocols being proposed for safety critical applications, such as Flex-Ray. In contrast with previous group membership protocols for TDMA-based networks, ours does not require the pre-allocation of group membership traffic in every cycle. Currently we are working on the formal verification of its correctness using the UPPAAL model checker. This will provide a higher assurance of correctness of the protocol, which is of foremost importance in safety critical applications.